Flood induced vulnerability to poverty: Evidence from Brahmaputra Valley, Assam, India. (September 2017) - Mahanta, Ratul; Das, Daisy
Abstract: This paper attempts to assess household vulnerability to poverty due to flood in Assam. Whether coping measures can reduce vulnerability and what factors affect such coping has also been examined. Applying vulnerability as expected poverty (VEP) approach to data collected through a primary survey of 476 households in 2013, the study finds that almost 83% of these households are vulnerable to poverty due to flood. The results show that incidence of poverty, flood height and use of coping strategies play significant role in determining households' vulnerability to poverty. The study also suggests that institutional factors, household's socio-economic conditions and community characteristics determine the use of coping strategies at the household level. Highlights: Flood induced vulnerability to poverty. Flood in Brahmaputra Valley, Assam, India. Flood and Coping strategies in Assam, India.